Methods replacing speech for people with dumbness deformity الوسائل التي تقوم مقام الكلام للمصابين بعاهة الخرس - Mohd Fadzhil, Mustafa; Mohamed Fathy, Mohamed Abdelgelil; Waleed, Ahmed Hashem (2019)
People with deformities have many rulings because these deformities may affect their lives. These may cause symptoms and inhibitions, which diminish their eligibilities for performance and make their body organs and members impotent. The problem of the research lies in the proposition that if the disabled organs is removed or insufficient, does it have an alternate that is able to perform what it could not. Should it be considered like the original member or not? Do all deformities have alternates? The importance of this research is manifested for this reason. The researcher focuses on the methods which substitutes the deformity of dumbness through which man wholly lost his ability to speech is no more considered. The researcher adopted the inductive and deductive methodology. The results he found that nothing can replace the deformed member except for the member of speech which be replaced writing and pointing.